2023
DOI: 10.3390/metabo14010018
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Changes in Plasma of Preterminal Stage of Rhesus Nonhuman Primates Exposed to Lethal Dose of Radiation

Alana D. Carpenter,
Oluseyi O. Fatanmi,
Stephen Y. Wise
et al.

Abstract: Ionizing radiation exposure is known to induce molecular and cellular injury, inflicting a cascade of potentially catastrophic events leading to tissue and organ damage. Metabolomic analysis allows for the identification and quantification of small molecules downstream of genomic changes induced by radiation exposure. We aimed to characterize metabolomic changes that underscore the prefinal stage of lethally irradiated rhesus nonhuman primates (NHPs). Peripheral blood was drawn at baseline, post-exposure, as w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…We have also performed metabolomics analysis on plasma samples collected throughout the course of this study at the same time points, which also demonstrated that radiation induced signi cant time-dependent metabolic perturbations when compared to pre-irradiation pro les. A distinguishable preterminal phenotype was observed, with notable dysregulation in metabolites related to the glycerophospholipid metabolism and steroid hormone biosynthesis and metabolism pathways 21 . Notably, metabolomic and proteomic preterminal signatures were demonstrated in both of these studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have also performed metabolomics analysis on plasma samples collected throughout the course of this study at the same time points, which also demonstrated that radiation induced signi cant time-dependent metabolic perturbations when compared to pre-irradiation pro les. A distinguishable preterminal phenotype was observed, with notable dysregulation in metabolites related to the glycerophospholipid metabolism and steroid hormone biosynthesis and metabolism pathways 21 . Notably, metabolomic and proteomic preterminal signatures were demonstrated in both of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…These NHPs were housed in a facility accredited by the Association for Assessment and Accreditation of Laboratory Animal Care (AAALAC)-International and underwent quarantine for seven weeks. Details of animal care are described earlier 21 . The study design and animal procedures were approved by The Institutional Animal Care and Use Committee and the Department of Defense Animal Care and Use Review O ce (ACURO).…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 ). Plasma samples were collected pre-irradiation (day -7), at 1, 13, and 25 days post-irradiation, and immediately prior to death in a subgroup of moribund animals (termed “preterminal” samples) 21 . The comparative analysis of the plasma proteomic profiles at various time points was central to this investigation, as it provides insight into the temporal dynamics of radiation-induced biological alterations.…”
Section: Introductionmentioning
confidence: 99%